Genetic Diversity, Virulence, Race Profiling, and Comparative Genomic Analysis of the Fusarium oxysporum f. sp. conglutinans Strains Infecting Cabbages in China - Liu, Xing; Xing, Miaomiao; Kong, Congcong; Fang, Zhiyuan; Yang, Limei; Zhang, Yangyong; Wang, Yong; Ling, Jian; Yang, Yuhong; Lv, Honghao (Frontiers in Microbiology, 2019)
Cabbage Fusarium wilt (CFW) caused by Fusarium oxysporum f. sp. conglutinans (FOC) is known to significantly affect yield and quality of cabbage worldwide. CFW was first detected in New York, US and has now spread to almost all cabbage-planting areas including a recent outbreak of the disease in China. However, it was unknown whether the FOC strains emerged in China differed from the strains in other areas of the world. From 2009-2018, we collected Chinese FOC isolates, and compared them to the races 1 and 2 strains in other areas to define their characteristics. Race tests indicated that most of the Chinese FOC strains belonged to race 1 and were more virulent than the type strain 52557. To evaluate the genome level diversity, we performed next-generation sequencing (NGS) and genome assembly for the race 2 strain 58385. Based on the assembled genome, we discovered abundant single nucleotide polymorphisms (SNPs) and 645 insertion-deletions (InDels) compared with the race 1 strain FGL03-6 by comparative genomic analysis, and showed all FOC race 1 strains have a low genetic variability with a genomic background distinct from 58385. Furthermore, the ITS, EF-1α and whole-genome InDel variation studies suggested that the last might be a powerful tool in phylogenetic as well as evolution analysis for FO. The race, virulence and genome based variation profiles could contribute to our knowledge of FOC diversity and support the studies of pathogen characterization in genomic era and also provide clues for CFW-resistance breeding. To our knowledge, this is the first extensive survey conducted for FOC strains.